Molecular and cellular basis of mu-opioid receptor signaling: mechanisms underlying tolerance and dependence development - Swingler, Michael; Donadoni, Martina; Unterwald, Ellen M.; Maggirwar, Sanjay B.; Sariyer, Ilker K. (Frontiers in Neuroscience, 2025)
Opioids, while highly effective for pain management, are among the most addictive substances, contributing significantly to the global opioid crisis. Opioid use disorder (OUD) affects millions, with synthetic opioids like fentanyl exacerbating the epidemic due to their potency and widespread illicit availability. Opioids exert their effects through opioid receptors (ORs), primarily the mu opioid receptor (MOR), which mediates both therapeutic analgesia and adverse effects such as euphoria, dependence, and tolerance. Chronic opioid use leads to cellular adaptations, including receptor phosphorylation, desensitization, and recruitment of β-arrestin, which uncouple MOR from downstream signaling pathways. These changes, along with compensatory upregulation of adenylyl cyclase (AC) and cAMP signaling, underlie the development of tolerance, dependence, and withdrawal, however the exact signaling pathways responsible remain unknown. Emerging research highlights the role of neuroinflammation, genetic polymorphisms, and alternative splicing of MOR isoforms in modulating opioid responses and vulnerability to OUD. Current treatments for OUD, such as methadone, buprenorphine, and naltrexone, are limited by compliance, access, and relapse rates. Novel therapeutic strategies, including biased MOR agonists, opioid vaccines, and splice variant-specific agonists, offer promise for safer pain management and reduced abuse liability. However, a deeper understanding of opioid receptor signaling, neuroimmune interactions, and genetic factors is essential to develop more effective interventions. This review explores the molecular mechanisms of opioid tolerance, dependence, and withdrawal, emphasizing the need for innovative approaches to address the opioid crisis and improve treatment outcomes.